Analysis of Japanese Jōmon period red lacquerwares by pyrolysis gas chromatography/mass spectrometry. (April 2018) - Takahashi, Shinichi; Sung, Meesook; Honda, Takayuki; Lu, Rong; Jung, Jaekook; Miyakoshi, Tetsuo
Abstract: Sixteen lacquerwares excavated from the Minamikonuma ruins located in Saitama City, Saitama Prefecture, Japan, were analyzed by mean of cross-section observation, attenuated total reflection Fourier transform infrared spectroscopy (ATR-FT/IR), energy dispersive X-ray fluorescence (EDXRF), and pyrolysis gas chromatography/mass spectrometry (Py-GC/MS). The results showed that Fe2 O3 was used as a red pigment in the relatively cheap lacquerwares or in the under layers, and HgS was used as another red pigment in an advanced stage. The characteristic urushiol products were detected in direct and derivative pyrolysis GC/MS of all sixteen lacquerwares and suggested that these Jōmon period lacquerwares were coated with lacquer sap collected from Toxicodendron vernicifluum lacquer trees. Highlights: Sixteen Japanese Jōmon period red lacquerwares were identified by Py-GC/MS. Fe2 O3 was found to be used as a red pigment in the relatively cheap lacquerwares and HgS in an advanced stage by EDXRF analysis. Coating layer structures were revealed by cross-section and ATR-FT/IR methods.